Evaluating Adaptive Assessment Models for Children with Special Needs in Christian Religious Education: A Mephibosheth-Inspired Hermeneutical Framework - Novalyn Olly Tuegeh; Dicky Welly Kansil; Gilbert Timothy Majesty (International Perspectives in Christian Education and Philosophy, 2026)
The evaluation of adaptive assessment models for children with special needs within Christian Religious Education (CRE) presents unique pedagogical and theological challenges. Standardized assessments often fail to accommodate diverse cognitive, emotional, and physical abilities, inadvertently excluding these learners from meaningful spiritual evaluation. This article proposes a constructive and hermeneutical method to develop an alternative evaluative framework inspired by the biblical narrative of Mephibosheth (2 Samuel 9). Constructively, the study synthesizes principles from special education specifically Universal Design for Learning (UDL) and differentiated assessment with a theological anthropology grounded in imago Dei. Hermeneutically, the Mephibosheth narrative is reinterpreted not as a passive recipient of charity but as a paradigmatic figure whose "crippled feet" symbolize both vulnerability and dignified inclusion under divine grace. The resulting framework redefines assessment success not by normative performance metrics but by relational engagement, progress relative to individual capacity, and the affirmation of inherent worth before God. Key evaluative components include flexible modalities (verbal, artistic, kinesthetic), process-oriented feedback, and community-based affirmation. This Mephibosheth-inspired approach transforms assessment from a tool of exclusion into a means of grace, offering a theologically robust and pedagogically practical model for CRE practitioners to faithfully serve children of all abilities.